2007
DOI: 10.1007/s00405-007-0246-8
|View full text |Cite
|
Sign up to set email alerts
|

Histologic assessment of epithelial thickness in early laryngeal cancer or precursor lesions and its impact on endoscopic imaging

Abstract: The objective of the study was to assess the epithelial thickness in different lesions of the vocal folds in order to gain more information about its influence on endoscopic imaging. Retrospective study including 161 patients undergoing surgery for a total of 206 benign and malignant lesions of the vocal folds. Laryngoscopy and autofluorescence endoscopy were the first line of investigation for these lesions. Diagnosis was confirmed by histopathology in all cases. Morphometric measurement of epithelial thickne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
42
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 11 publications
4
42
1
1
Order By: Relevance
“…In regard to the diagnostic utility of WLE, Caffier et al (196) showed a higher accuracy for WL (97% vs. 81%) than AFE and AFE data analysis provided a reduction in specificity of 25% in comparison to WLS, together with a high false positive value (31%). These findings were in accordance with literature reports (197,198). On the other hand, even if Crosetti et al (199) confirmed that sensitivity and specificity of AFE in distinguish between benign and dysplastic/ neoplastic lesions are negatively impacted by different features (i.e.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In regard to the diagnostic utility of WLE, Caffier et al (196) showed a higher accuracy for WL (97% vs. 81%) than AFE and AFE data analysis provided a reduction in specificity of 25% in comparison to WLS, together with a high false positive value (31%). These findings were in accordance with literature reports (197,198). On the other hand, even if Crosetti et al (199) confirmed that sensitivity and specificity of AFE in distinguish between benign and dysplastic/ neoplastic lesions are negatively impacted by different features (i.e.…”
Section: Resultssupporting
confidence: 91%
“…In attention to avoid false positive and false negative findings, we recommended simultaneous careful comparison of white light and autofluorescent images of same view. Both effects: (1) epithelial thickening of (pre)malignant tissue with inhibited penetration of exciting light into submucous layers and (2) the altered metabolism of tumor cells with lower concentration of NADH and FAD, are claimed to be mainly responsible for the reduced total AF in neoplastic laryngeal tissue (197). These considerations are basic as far as concerns the application field of this method.…”
mentioning
confidence: 99%
“…Wir unterscheiden zwischen EBV, die sich in vertikale und horizontale sowie zelluläre Ausbreitungsdiagnostik differenzieren, wobei sich die konfokale Endomikroskopie (KOM) in 2 Gruppen einordnen ließe. [10].…”
Section: Fortschritte Der Endoskopischen Diagnostik Von Dysplasien Ununclassified
“…For instance, the thickening of epithelium in the vocal folds is an indicator of early laryngeal cancer (Arens et al 2007). Another example is the measurement of the central corneal thickness that can be related to the intraocular pressure (IOP) to determine onset of glaucoma (Ehlers et al 1975).…”
Section: Introductionmentioning
confidence: 99%